2015
DOI: 10.1590/2359-3997000000014
|View full text |Cite
|
Sign up to set email alerts
|

Is Doppler ultrasound of additional value to gray-scale ultrasound in differentiating malignant and benign thyroid nodules?

Abstract: SUMMARYThe objective of this study was to evaluate whether Doppler ultrasound (DUS) is of additional value to gray-scale ultrasound (GSUS) in predicting the benign or malignant nature of thyroid nodules. A total of 1,502 solid thyroid nodules ≥ 10 mm were evaluated. Suspicious vascularity (predominantly or exclusively central blood flow) was observed in only 5% of the nodules. This finding showed 96% specificity, but only 15% sensitivity. GSUS alone showed sensitivity and specificity of 88.7% and 68.2%, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 27 publications
5
28
1
1
Order By: Relevance
“…The "undefined" category corresponded to iso-or hyperechoic nodules with some suspicious finding, that is, irregular margins, microcalcifications, a taller than wide shape, and rim calcifications with a small extrusive soft tissue component [16]. The type of blood flow of all thyroid nodules was evaluated before FNA: type 0, no vascularity; type 1, peripheral vascularity; type 2, peripheral and intranodular vascularity; type 3, exclusively or predominantly intranodular vascularity, which is considered suspicious of malignancy [12,[17][18][19]. US/Doppler was performed by radiologist experienced in thyroid imaging (A.L.S.)…”
Section: Methodsmentioning
confidence: 99%
“…The "undefined" category corresponded to iso-or hyperechoic nodules with some suspicious finding, that is, irregular margins, microcalcifications, a taller than wide shape, and rim calcifications with a small extrusive soft tissue component [16]. The type of blood flow of all thyroid nodules was evaluated before FNA: type 0, no vascularity; type 1, peripheral vascularity; type 2, peripheral and intranodular vascularity; type 3, exclusively or predominantly intranodular vascularity, which is considered suspicious of malignancy [12,[17][18][19]. US/Doppler was performed by radiologist experienced in thyroid imaging (A.L.S.)…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, biopsy was relied on to get the final diagnosis, and is considered the diagnostic criterion standard [8, 9], but biopsy is invasive and has some risk for patients. Previous studies showed that 48–75% of patients who undergo biopsy are subsequently found to have benign lesions [10,11], the overall dissatisfaction rate for FNA is between 10–20% [12], and 2% of samples obtained by CNB are inadequate for histological diagnosis [8]. How to reduce the number of unnecessary biopsies is an area of current research.…”
Section: Introductionmentioning
confidence: 99%
“…Although a higher frequency of nodules with exclusively or predominantly intranodular vascularity (type 3) on Doppler US was observed in iEFVPTC, the difference was not significant. This vascularity, which is suspicious of malignancy, 4,7 was found in a minority of nodules that were NIFTP, but was also uncommon in iEFVPTC. Thus, NIFTP is very similar to iEFVPTC in terms of Doppler US appearance.In conclusion, Doppler US does not contribute to the distinction between NIFTP and iEFVPTC.…”
mentioning
confidence: 89%
“…2 The type of blood flow of all thyroid nodules was evaluated before FNA: type 0, no vascularity; type 1, peripheral vascularity; type 2, peripheral and intranodular vascularity; type 3, exclusively or predominantly intranodular vascularity, which is considered suspicious of malignancy. 4,7 Fisher's exact test or the chi-squared test was used to detect differences in the proportion of cases. A P-value of <.05 was considered to be significant.…”
mentioning
confidence: 99%